The Impact of the 2016 Turkish Military Coup on Politics in Turkey - Ismail Adsay (GoAcademica Research & Publishing, 2020)
On July 15, 2016, a Military Coup took place in Turkey to overthrow President Recep Tayyip Erdogan's government. Although the coup failed, certainly not an advantage for Turkey, which is the government trying to increase political, economic and social stability in Turkey. This paper examines the impact of the 2016 Turkish military coup on Turkish politics by focusing on its impact on domestic politics in Turkey. The approach in research uses literature review. The data collection technique of this research is literature study using secondary data with descriptive analysis. The results of this study describe that domestic politics, the coup has an impact on government relations with opposition parties, the democratic climate, political policy and military bureaucracy.